2006
DOI: 10.1080/10640260600796184
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Body Dissatisfaction and Disordered Eating: What Next?

Abstract: Eating disorder prevention is a young field that has made significant strides in the past two decades. It is timely to take a look back at what we have learned during this period in order to begin to address the question, "What next?" This paper considers several key issues based upon a review of the literature and the authors' perspectives. Topics discussed include: (1) environmental approaches; (2) global mental health versus eating disorder specific interventions; (3) participatory approaches; (4) the integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
0
8

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(106 citation statements)
references
References 58 publications
1
97
0
8
Order By: Relevance
“…Many of the traditional obesity prevention programmes, largely designed and carried out by experts in obesity with little or no background in other fields such as those of body image or ED, basically focus on physical activity, diet and weight control. Thus, unintentionally, the increased investment in the prevention of obesity could have negative effects on areas such as body image, dieting, weight-related teasing, excessive weight preoccupation and other risk factors for ED, cancelling out the efforts and achievements in the field of the prevention of disordered eating and body dissatisfaction (53,57,58) . A very clear example of this would be some of the measures being adopted in schools -such as periodic assessments of BMI -with the aim of identifying overweight children and reporting back to parents by letter, advising dietary changes and physical activity or that the child should see a doctor.…”
Section: Prevalence Of Eating-and Weight-related Problemsmentioning
confidence: 99%
“…Many of the traditional obesity prevention programmes, largely designed and carried out by experts in obesity with little or no background in other fields such as those of body image or ED, basically focus on physical activity, diet and weight control. Thus, unintentionally, the increased investment in the prevention of obesity could have negative effects on areas such as body image, dieting, weight-related teasing, excessive weight preoccupation and other risk factors for ED, cancelling out the efforts and achievements in the field of the prevention of disordered eating and body dissatisfaction (53,57,58) . A very clear example of this would be some of the measures being adopted in schools -such as periodic assessments of BMI -with the aim of identifying overweight children and reporting back to parents by letter, advising dietary changes and physical activity or that the child should see a doctor.…”
Section: Prevalence Of Eating-and Weight-related Problemsmentioning
confidence: 99%
“…Eating disorders is still a relatively new field and a greater understanding of interpersonal risk factors and protective factors is needed [12]. Health education programs that target low self-efficacy and body dissatisfaction are critical and they are currently lacking [5].…”
Section: Discussionmentioning
confidence: 99%
“…High self-efficacy has been associated with successful weight loss and maintenance throughout the literature [10]; whereas, negative emotions concerning treatment contribute to the perpetuation of eating disorders [11]. Alternatively, bolstering self-efficacy may be a protective factor for eating disorders since some Diet self-effi cacy and physical self-concept of college students at risk for eating disorders studies indicate low self-efficacy may contribute to issues with body image and eating [12]. Individuals with high self-efficacy may show more persistence and better-coping strategies to face challenges than their counterparts [10,13].…”
Section: Introductionmentioning
confidence: 99%
“…Although the selective prevention field has made some important steps in this area (Müller & Stice, 2013;Stice, Marti, Shaw, & O'Neil, 2008b;Stice, Rohde, Gau, & Shaw, 2012;Taylor, et al, 2006), research focus needs to also be directed to moderators of universal interventions in order to understand what might influence the outcome of long-term universal prevention trials. It has been suggested that ideally, eating disorder prevention should operate across a spectrum where pre-and early-adolescents receive empiricallyinformed universal programs where those requiring additional input might later benefit from participation in selective and targeted programs (Neumark-Sztainer, et al, 2006;Wilksch & Wade, 2009b). Thus it is important that the universal approach not be overlooked in our collective efforts to prevent eating disorders and to the best of our knowledge, the current study is the first to investigate individual participant variables that might moderate program outcome of a universal eating disorder prevention program.…”
Section: Introductionmentioning
confidence: 99%